Decision Support System on Effect of Variable Attitude and Skills and Knowledge Construction Workers on Softskills and Hardskills - Ariadi, Riki; Darmana, I (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
In the world of construction services, employee performance is one determinant in measuring the productivity of the success of the construction project. Therefore, the performance of the worker is determined on three variables: attitude, skills and knowledge. This contribution is to be a perspective that should be owned by construction workers today, many concerns that occur in the field, the workers experienced various difficulties in the face of performance, because it is very shallow mastered these three things, so the implementation in running the project encountered many obstacles that lead to productivity performance is greatly decreased. Standard competence of workers in this era are highly demanded on softskills (1) consisting of interpersonal skills (a) and intrapersonal skills (b) and hardskills (2) consisting of transforming character (a), change management (b), stress management (c), time management (d). so, that the variables can be evaluated and analyzed through decision systems (decision support system) to make the performance of workers more productive and efficient on target (cost, quality and time).